Synthesis, characterization, conduction and gas sensing properties of novel multinuclear metallo phthalocyanines (Zn, Co) with alkylthio substituents - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
Compound 1 has been prepared by the reaction of 4-nitrophthalonitrile and 2-nitro-2-methyl-1,3-propanediol by the common method of nucleophilic substitution of an activated nitro group in an aromatic ring. Interesting binuclear metallophthatocyanines (M = Zn and Co), compounds 2 and 3, respectively, of a new type have been synthesized from compound 1, 4,.5-bis(hexylthio)phthalonitrile, and the corresponding metal salts [Zn(OAC)(2) and CoCl2] by the method of statistically mixed condensation. Compound 2 was converted to the tetranuclear zinc (II) phthalocyanine 4 by the reaction with NaOH solution and activated zinc powder in a mixture of MeOH and THF as the solvent. Impedance spectroscopy (IS) and d.c conductivity (sigma(d.c)) measurements were performed on spin coated films of these compounds as a function of temperature (290-400 K) and frequency (40-10(5) Hz.) The sensing properties for volatile organic compounds (VOCs) were also investigated. Although the d.c conductivity shows typical Arrehenius behaviour for compound 2, a discontinous point was observed in the slope of ln sigma(d.c) versus 1/T plot for compound 4. Unlike the films of 2 and 4, the d.c behaviour of compound 3 obeys the variable range hopping (VRH) model. At room temperature, a curved line was observed from the complex plane plots of impedance for all compounds. These curved lines transformed into a full semicircle with increasing temperature. The a.c conductivity of the films is represented by the form omega(s). The dependency of the frequency exponent s on temperature suggests a correlated barrier hopping. A sensor using compound 4 as the sensing layer had the highest sensitivity for all volatile organic compounds investigated and showed complete reversibility even at room temperature. The results indicated that the film of compound 4 has potential as a sensitive coating for the monitoring of VOC vapours. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: phthalocyanine; VOC sensing; variable range hopping; CBH; COPPER PHTHALOCYANINE; ELECTRICAL-PROPERTIES; THIN-FILMS; ELECTROCHROMISM; MONONUCLEAR; REDUCTION; GLASSES; ACID